T.M. Cleland papers - Cleland, T. M. (Thomas Maitland), 1880-1964.
Correspondence, speeches, writings, project files, drawings, designs, and other papers relating primarily to Cleland's career as an artist, illustrator, printer, type designer, and typographer. Chiefly correspondence with publishers, clients, and fellow artists and printers. Attachments to correspondence include Cleland's original drawings, designs, typographical arrangements, specifications, and corrected proofs for books. Includes examples of his designs for bookplates, emblems, and insignia designed for clients such as the Century Club, Grolier Club, and Metropolitan Museum of Art. Correspondents include Frank Altschul, Fred Anthoensen, Merle Armitage, Boris Artzybasheff, Peter Beilenson, Paul A. Bennett, George Biddle, Will Bradley, Abraham Colish, Joseph Cotten, Arthur Sinclair Covey, Robert L. Dothard, Fritz Eichenberg, Montague Glass, Alfred E. Hamill, Alger Hiss, Ralph Ingersoll, Rockwell Kent, Fritz Kredel, George Macy, Francis Meynell, Joseph Pennell, Bruce Rogers, Rudolph Ruzicka, Oliver Simon, Edward A. Wilson, and Daniel Berkeley Updike, founder of Merrymount Press.
Family correspondence consists primarily of letters Cleland received from his wife, Elinor Woodruff Cleland, and includes material pertaining to Cleland family genealogy.
Book designer and illustrator.
Collection material in English, French, and Swedish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Altschul, Frank, -- 1887-1981 -- Correspondence; Anthoensen, Fred, -- 1882-1969 -- Correspondence; Armitage, Merle, -- 1893-1975 -- Correspondence; Artzybasheff, Boris, -- 1899-1965 -- Correspondence; Beilenson, Peter, -- 1905-1962 -- Correspondence; Bennett, Paul A., -- 1897-1966 -- Correspondence; Biddle, George, -- 1885-1973 -- Correspondence; Bradley, Will, -- 1868-1962 -- Correspondence; Cleland, Elinor Woodruff, -- 1871- -- Correspondence; Colish, Abraham, -- 1882-1963 -- Correspondence; Cotten, Joseph, -- 1905-1994 -- Correspondence; Covey, Arthur Sinclair, -- 1877-1960 -- Correspondence; Dothard, Robert L. -- Correspondence; Eichenberg, Fritz, -- 1901-1990 -- Correspondence; Glass, Montague, -- 1877-1934 -- Correspondence; Hamill, Alfred E. -- 1884-1953 -- Correspondence; Hiss, Alger -- Correspondence; Ingersoll, Ralph, -- 1900-1985 -- Correspondence; Ingersoll, Ralph, -- 1900-1985 -- Correspondence; Kredel, Fritz, -- 1900-1973 -- Correspondence; Macy, George -- Correspondence; Meynell, Francis, -- 1891-1975 -- Correspondence; Pennell, Joseph, -- 1857-1926 -- Correspondence; Rogers, Bruce, -- 1870-1957 -- Correspondence; Ruzicka, Rudolph, -- 1883-1978 -- Correspondence; Simon, Oliver, -- 1895-1956 -- Correspondence; Updike, Daniel Berkeley, -- 1860-1941 -- Correspondence; Wilson, Edward A. -- 1886-1970 -- Correspondence; Cleland family; Cleland family -- Correspondence; Century Club (New York, N.Y.); Grolier Club; Merrymount Press; Metropolitan Museum of Art (New York, N.Y.); Art; Book design; Bookplates; Emblems; Graphic design (Typography); Illustration of books; Insignia; Printing; Publishers and publishing; Book designers; Illustrators